2021
DOI: 10.1109/tcsi.2021.3083280
|View full text |Cite
|
Sign up to set email alerts
|

Towards Low Latency and Resource-Efficient FPGA Implementations of the MUSIC Algorithm for Direction of Arrival Estimation

Abstract: The estimation of the Direction of Arrival (DoA) is one of the most critical parameters for target recognition, identification and classification. MUltiple SIgnal Classification (MUSIC) is a powerful technique for DoA estimation. The algorithm requires complex mathematical operations like the computation of the covariance matrix for the input signals, eigenvalue decomposition and signal peak search. All these signal processing operations make real-time and resource-efficient implementation of the MUSIC algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 26 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Based on [39,40], the validation of the proposed CbSS technique can be carried out using field programmable gate array (FPGA) prototyping platforms. In past DOA estimation literature, such as [39,41], practical experiments have demonstrated that it can meet real-world applications with sufficient computational complexities of the same subspace-based class of DOA estimators. In addition, a comprehensive comparison and performance analysis against geometric-based DOA estimators can be carried out to compare the estimation robustness and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on [39,40], the validation of the proposed CbSS technique can be carried out using field programmable gate array (FPGA) prototyping platforms. In past DOA estimation literature, such as [39,41], practical experiments have demonstrated that it can meet real-world applications with sufficient computational complexities of the same subspace-based class of DOA estimators. In addition, a comprehensive comparison and performance analysis against geometric-based DOA estimators can be carried out to compare the estimation robustness and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm was simulated to work up to 1 GHz clock frequency, on a TMSC 40-nm CMOS technology. In [16], Butt et al implemented an optimized version of the MUSIC algorithm with reduced processing time and resource occupation using a Xilinx FPGA The improvement is obtained by normalizing the covariance matrix and reducing its size by considering only three adjacent antennas and then choosing to evaluate the best-received signal level. The estimation takes a few µs.…”
Section: Related Workmentioning
confidence: 99%
“…With the challenge of creating an audio-only sensor system to localize and identify speakers without requiring a video-based solution, this work presents an embedded, costeffective, low-power, and real-time microphone array solution for speaker localization and identification that can be used inside an SAV. To accelerate the processing tasks, the sensor system resorts to Field-Programmable Gate Array (FPGA) technology to deploy dedicated processing modules in hardware to interface, acquire, and compute data from different microphones [44][45][46][47][48][49]. Moreover, the processing system provides a Robot Operating System (ROS) interface to make data available to other high-level applications (for the identification and classification of audio events) or to other sensor fusion systems.…”
Section: Introductionmentioning
confidence: 99%